Migrants’ Experiences of Accessing Primary Care in Emfuleni Municipality, South Africa - Reitumetse Thulo; Christian Lokotola; Robert Mash (Journal of Primary Care & Community Health)
Introduction: Universal health coverage promotes equity of access to essential health care for all, including migrants. Health systems struggle to balance global commitments to health equity with national concerns for sovereignty and security. Migrants therefore often experience inequitable access to primary care. Objectives: To explore migrants’ experience in accessing public sector primary care services in Emfuleni subdistrict, Gauteng, South Africa. Methods: A descriptive exploratory qualitative research study purposefully selected migrants and gathered data using semi-structured interviews in English, French and Portuguese. Data was thematically analysed using the framework method assisted by Atlas-ti. Results: Fifteen migrants were interviewed. Four main themes were identified. (1) Barriers related to legal status, financial constraints, language issues and misinformation. (2) Coping strategies that included social support, traditional beliefs and alternative practitioners. (3) Healthcare experiences that included good quality care as well as denial of care and delayed care. (4) Psychosocial and emotional effects related to stigmatisation, discrimination and mental health problems. Conclusions: This study sheds light on the significant obstacles that migrants have while trying to use government clinics in Gauteng, South Africa. The health system should address these factors through policy, protocols, translation services, training of staff and clear messaging in the migrant community.